Eyebrow colour in diabetics - Wollina, Uwe (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Background. Hair colour may be affected by a metabolic disease. Systematic investigations in diabetics are missing. Objective. A clinical study was performed to evaluate whether dark colour of eyebrows in greying males is associated with diabetes or not. Setting. Academic teaching hospital, inpatient and outpatient department. Methods. In an uncontrolled analysis two groups of male patients between 50 to 70 years of age were investigated for evidence of diabetes mellitus. Inclusion criteria we're original scalp hair colour brown to black with more than 50% greying hair, no chemotherapy, hormone (except insulin) or interferon treatment, current or previous, no artificial colouring of hair, and absence of total alopecia. Group A consistedof 50 males with dark eyebrow colour, group B of 50 males with greying of eyebrows. A careful medical history and clinical examination was performed. In patients without known diabetes, blood sugar levels (profile during the day) and HbA1 c were evaluated. Results. In group A 38 of 50 patients (76 %) were diabetics type II. The mean duration of diabetes was 3.4 years (SD 6.8 years; range 1 year to 31 years). Six patients were diagnosed ashaving diabetes for the first time. In group B 9 of 50 patients (18%) were diabetics, two of type I and 7 of type II. One patient with a newly detected diabetes type II was seen. The mean duration of diabetes was 4.1 years (SD 7.6years; range: 1 year to 39 years). The difference in diabetes frequency is statistically highly significant (two-sided t-test: p<0.0001). Odds ratios (OR) for diabetes are higher in greying males with dark eyebrows (OR 3.17) vs.those with greying eyebrows and scalp hair (OR 0.19) in this age group. Conclusions. In male diabetics at the age of 50 years or more greying of the eyebrows seems to be inhibited or delayed. The presence of dark eyebrows with greying scalp hair in males might be a clinical sign for patients at risk of diabetes type II.
Keywords: barva; Diabetes Mellitus; Eyebrows; Hair Color; Lasje, barva; Obrvi; Sladkorna bolezen